The complement system in cancer: ambivalence between tumour destruction and promotion - Mamidi, Srinivas; Höne, Simon; Kirschfink, Michael (Immunobiology, 2017)
Constituting a part of the innate immune system, the complement system consists of over 50 proteins either acting as part of a 3-branch activation cascade, a well-differentiated regulatory system in fluid phase or on each tissue, or as receptors translating the activation signal to multiple cellular effector functions. Complement serves as first line of defence against infections from bacteria, viruses and parasites by orchestrating the immune response through opsonisation, recruitment of immune cells to the site of infection and direct cell lysis. Complement is generally recognised as a protective mechanism against the formation of tumours in humans, but is often limited by various resistance mechanisms interfering with its cytotoxic action, now considered as a great barrier of successful antibody-based immunotherapy. However, recent studies also indicate a pro-tumourigenic potential of complement in certain cancers and under certain conditions. In this review, we present recent findings on the possible dual role of complement in destroying cancer, especially if resistance mechanisms are blocked, but also under certain inflammatory conditions—promoting tumour development.